PENGARUH MODEL PEMBELAJARAN ARCS TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMK - Suhardi, Dinda Agustin (Departemen Matematika, 2023)
The ability to solve mathematical problems is needed as a reference in solving a problem related to everyday life and also to get used to managing different problems. However, when viewed based on phenomena in the world of education, this problem-solving ability is still not paid enough attention to by students and schools. The results of the initial test conducted in class XI at SMK Negeri 3 Payakumbuh, it was stated that there were still many who had not been able to solve the problem properly and correctly. The countermeasures carried out to overcome this problem are by applying the ARCS learning model. The research intends to find out whether it is possible for disciples who are taught with the ARCS learning model to have better problem-solving skills than disciples who are taught with the Problem Based Learning model in class XI at SMK Negeri 3 Payakumbuh. This research is a quasi-experimental typewith The Static Group Comparison Design. The population is class XI students of SMK Negeri 3 Payakumbuh. The test instrument for problem solving abilities is in the form of an essay. Based on data processing using the t-test, a P-value = 0.000 is obtained that means reject H0. So that the results were obtained that students who implemented the ARCS model had better problem solving abilities than students who implemented the Problem Based Learning model in class XI SMK Negeri 3 Payakumbuh.Keywords- ARCS, Problem solving, Mathematic